1989
DOI: 10.1557/jmr.1989.1246
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of nanophase TiO2

Abstract: Raman spectra are reported for consolidated nanophase TiO2 particles in their as-compacted state and after annealing at a variety of temperatures up to 1273 K. The Raman-active bands normally observed for the rutile form of TiO2 were present in as-compacted samples having average grain sizes in the range from about 10 to 100 nm. However, significant broadening of these bands was found, which was uncorrelated with initial grain size, but not necessarily with other synthesis-related factors. This broadening decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(98 citation statements)
references
References 14 publications
11
86
1
Order By: Relevance
“…[15,31] Bands characterizing anatase should appear at 395 cm ±1 , 515 cm ±1 , and 640 cm ±1 , while rutile demonstrates Raman peaks at 444 cm ±1 and 609 cm ±1 . Instead, the spectra obtained in the present study were shifted, and rather similar to those observed by Melendres et al [32] for finegrained (10±100 nm) TiO 2 particles. It can be seen that the films grown in the present study at 450 C yield Raman spectra demonstrating broad rutile bands at approximately 470 cm ±1 and 630 cm ±1 (Fig.…”
Section: Films On Glass Substratessupporting
confidence: 90%
“…[15,31] Bands characterizing anatase should appear at 395 cm ±1 , 515 cm ±1 , and 640 cm ±1 , while rutile demonstrates Raman peaks at 444 cm ±1 and 609 cm ±1 . Instead, the spectra obtained in the present study were shifted, and rather similar to those observed by Melendres et al [32] for finegrained (10±100 nm) TiO 2 particles. It can be seen that the films grown in the present study at 450 C yield Raman spectra demonstrating broad rutile bands at approximately 470 cm ±1 and 630 cm ±1 (Fig.…”
Section: Films On Glass Substratessupporting
confidence: 90%
“…Indeed, there is no occurrence of a Raman peak at precisely this wavenumber in an extensive catalogue of (transition and other) metal compounds [46] but it is interesting to note that a strong peak has been observed at 240 cm -1 in nanophase TiO 2 [47] which was not clearly identified but was attributed to a long range order effect, occurring when bands known to be characteristic of the crystal structure were strong. This is the case here, where for samples ZC3 and ZC4, the 241 cm -1 band displays virtually full recovery of the ZnO level, while ZC1 and ZC2 show almost no discernible feature at this wavenumber.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In the case of nanophase TiO 2 cited above , the oxygen deficiency, while still present, is rather small and easily remedied. Raman spectroscopy has been a useful tool in studying the oxidation state of nanophase TiO 2 owing to the intense and well studied Raman bands in both the anatase and rutile forms of this oxide and the observation that these bands were affected in nanophase samples (Melendres et al, 1989). Raman spectra of as-consolidated nanophase TiO 2 samples and fully annealed and oxidized TiO 2 are shown in Fig.…”
Section: Conventional Gas-condensation Methodsmentioning
confidence: 99%